The development and implementation of a performance management system: a case study - Whittington-Jones, Alexandra (Rhodes University, Faculty of Commerce, Investec Business School, 2005)
After a review of the literature relevant to performance management systems both over time and across different types of organizations, this thesis confines its research to a case study of the development and implementation of a performance management system in a non-governmental organization (NGO), the Public Service Accountability Monitor (PSAM). Collation of the relevant data is followed by a discussion of the development and implementation of the performance management system at the PSAM over a 5-year period from 1 June 1999 to 31 May 2004. This is considered in terms of the PSAM's achievement of commitments to Funders and the concurrent development of the performance management system. Next an analysis of major themes that emerged from the research, in terms of important items for consideration in the development and implementation of a performance management system in an NGO, and areas for possible future improvements to the system is presented. After analyzing the relevant information, it became apparent that the performance management system has no direct bearing on the ability of the PSAM to achieve its stated commitment to Funders. However, these short-term focused expectations of the performance management system are outweighed by the positive contributions that have been made by its introduction, specifically in the area of training and development. This important aspect of capacity building and staff empowerment speaks to the long term sustainability of the organization. Although the PSAM's performance management system undergoes continual improvement, significant inroads have been made into providing a sensible, clear and dynamic solution to the problem of rewarding efficient and effective performance. The PSAM has indeed benefited from the introduction of the performance management system in a number of ways. It is evident that these benefits could be applicable to other NGOs.
Keywords: Public Service Accountability Monitor (South Africa); Non-governmental organizations -- South Africa -- Evaluation; Performance -- Management -- Case studies; Organizational effectiveness -- Case studies